CAN SELF-EFFICACY MEDIATE RELATIONS BETWEEN HELICOPTER PARENTING AND SOCIAL MEDIA ADDICTION AMONG TURKISH ADOLESCENTS? - Asici, Esra; Uygur, S. Sevgi; Kocer, Merve (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2025)
This study aimed to investigate the mediating role of self-efficacy (social, emotional, and academic) in the relationship between helicopter parenting and social media addiction (SMA) among Turkish adolescents. Previous studies examining the influences of helicopter parenting behaviors on mental health mostly studied college-age children and were conducted in Western cultures, while the current study focused on the association of helicopter parenting with the mental health of younger children and was conducted an Eastern country (Türkiye). The participants consisted of 326 adolescents (212 girls and 114 boys) who had at least one social media account. Data were collected through the Helicopter Parent Attitude Scale, the Self-Efficacy Scale for Children, the Social Media Addiction Scale for Adolescents, and a demographic information form. Data were analyzed with descriptive statistics, Pearson correlation analysis, and regression-based bootstrapping techniques. The results show that both maternal and paternal helicopter parenting had significant and direct positive associations with SMA. Emotional and academic self-efficacy had significant and direct associations with SMA, while social self-efficacy did not show such an association. In addition, it was found that the mediating effects of self–efficacy (social, emotional, and academic) in relations between helicopter parenting and SMA were not significant.